The practice of the recreational basketball in children of 9-10 years in the community "Van Van" - Andrés Turro-Caro (Universidad de Guantánamo, 2014)
This work has as objective the development of a system of physical actions recreational sports for children in "Van Van" the community. Motivation and participation of children in the community, as well as allow you to enhance basketball practice and improve the quality of life. The proposed activities have a physical holistic education, which is supported on the basis of principles of physical education, and is a tool for the active, systematic and sustained physical activity recreational sports, widely useful for children living in the community.